Pelaksanaan Peraturan Daerah Kota Semarang Nomor 3 Tahun 2018 (Studi Tentang Penataan Dan Pemberdayaan Pedagang Kaki Lima Di Jalan Pandanaran II Kota Semarang) - Sari, Adinda Novita; Wisnaeni, Fifiana (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
Indonesia is a Republican State that has a variety of cultures, a maritime country with waters covering two-thirds of its land area, which makes it clear that Indonesia is a large country. The increasing number of poor people has resulted in an increasing number of people who prefer to work as street vendors because the work is in accordance with their expertise. The City Government has made efforts to reduce the difficulties caused by the presence of street vendors by passing Semarang City Regional Regulation Number 3 of 2018 concerning Arrangement and Empowerment of Street Vendors. The purpose of this research is to find out and examine the implementation of these regional regulations on Jalan Pandanaran 2 Semarang City, as well as the obstacles that hinder its implementation. The problems discussed in this study include how the Regional Regulation of the City of Semarang Number 3 of 2018 concerning Jalan Pandanaran II Semarang City is implemented, as well as the challenges faced. This research uses a juridical-empirical research type, the resources used consist of primary and secondary data. The research results obtained are (1) the implementation of this regional regulation can be said to have been going quite well even though it has not been implemented effectively. (2) there are still several obstacles encountered in the field such as lack of land availability, lack of human resources to support the effective implementation of regional regulations. (3) The solution that can be concluded from the results of interviews with several street vendors, the majority of them voiced a desire for the government to be more aggressive in providing socialization regarding a more orderly arrangement of street vendors, more accomodated collection of fees and clear coordination.